Legal English. The UN Convention on Genocide as a Domain-Specific Text - Gasparyan, Seda; Kharatyan, Lilit (Armenian Folia Anglistika, 2018)
The question of the interaction of language and law is one of the main issues occupying the minds of both the linguists and jurists of our time. The study of the intersection of these scientific fields acquires even more importance nowadays as expansion of economic and cultural cooperation between countries and within countries requires legal regulation, qualified assistance of lawyers and their participation in negotiations, business meetings and in the preparation of documentation. Accordingly, linguistic and translation activities in the sphere of legal relations turn out to be of special significance. Like other functional styles of speech, which are independent systems, the style of official documents has certain communicative goals as well as its own consistent patterns and language characteristics common to the given style. The latter are the subject of the present article.
Keywords: legal linguistics; a domain-specific language; legal English; the Genocide Convention as a legal text; language characteristics; layout features